Learning burnout of undergraduates and countermeasures analysis at Normal University - Xie, Hongyu; Xiao, He (American Journal of Creative Education, 2023)
This study aims to identify the main causes of learning burnout in university students and propose some solutions in order to improve the quality of education. Education quality and the development of high-caliber talents are strongly impacted by learning burnout among university students which is a reflection of their learning status and learning psychology. 400 students of different majors, grades and genders from three normal universities in Southwest China participated in this study. They were given questionnaires that included demographic information, study burnout status and causes of study burnout. Finally, 395 valid questionnaires were collected. Using IBM SPSS Statistics 22.0 software for statistical analysis(T-test), the results showed that there is a phenomenon of learning burnout among university students. There are significant differences in learning burnout in terms of gender, grade and major. Meanwhile, regression analysis demonstrates that each factor influences learning burnout to a different extent. In addition, burnout and its dimensions are significantly correlated with different factors such as professional factors, self-factors, peer factors, family factors, school factors and social factors. After analysis, the countermeasures to solve learning burnout were put forward. It is necessary to organically combine these six factors to form an educational network that integrates itself, family, school, society, etc.